O przekładach literatury polskiej w Czechach i czeskiej w Polsce. Komentarz do bibliografii przekładów w 2016 i 2017 roku - Altmann, Jakob (Przekłady Literatur Słowiańskich, 2019)
Presented article is a recapitulation of visible tendencies in both Polish and Czech publishing markets with regard to publications of literary translations of Czech literature in Poland and Polish literature in the Czech Republic in 2016 and 2017. It presents the most important literary translations in each language pair, pointing out leading publishers and the most active translators in this area. Finally, the author outlines general paths along which the Polish literature translations in the Czech Republic and vice versa develop.